Adherence to anti-epileptic medication in children with epilepsy from a Scottish population cohort. (24th May 2012) - Shetty, J; Kirkpatrick, M; Greene, S
Abstract : Objective: Adherence to treatment in many long-term conditions is recognised to be poor. Inadequate seizure control in epilepsy may therefore in some circumstances relate to poor adherence. There are only limited and methodologically flawed data on adherence in paediatric populations. Using a novel dataset for community pharmacy-dispensed medication we wished to assess the adherence to anti-epileptic drugs (AED) treatment both for individual children and for a whole population. We also aimed to correlate adherence with a series of clinical variables to identify factors that might predict adherence. Methods: All children under 16 from the Tayside region who were receiving AEDs during one year epochs in 2000/1 and 2005/6 were identified. The University of Dundee has a database which captures every encashed community pharmacy prescription in Tayside. An Adherence Index was calculated by cross-linking hospital data to university data. This data was available both cross-sectionally and longitudinally. Results: The overall adherence was 69% (n=320). However only 30% of children encashed >90% of the prescribed AED dose (defined as good adherers), whereas 25% encashed less than half. Amongst good adherers, 34% were on monotherapy and 18% were on polytherapy. Seizure frequency had no effect upon adherence whether a child was seizure free or continued to have multiple daily seizures. For children on long term AED treatment, mean adherence fell from 73% to 64% over a 5 year period and even for the good adherers there was a 50% fall in adherence between 2000 and 2006. Conclusions: We have described a novel population-based technique for assessing adherence to AED medication. Overall, adherence to treatment is poor and appears to be independent of seizure frequency. Adherence falls over time and is worse with polytherapy. Identification of these and other factors that might predict poor adherence may be helpful in the design and evaluation of interventions to improve epilepsy treatment.